2010
DOI: 10.1534/genetics.110.117929
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Culture-Induced Novel Epialleles of aMybTranscription Factor Encoded bypericarp color1in Maize

Abstract: Plants regenerated from tissue culture often display somaclonal variation, that is, somatic and often meiotically heritable phenotypic variation that can result from both genetic and epigenetic modifications. To better understand the molecular basis of somaclonal variation, we have characterized four unique tissue culture-derived epialleles of the pericarp color1 (p1) gene of maize (Zea mays L.). The progenitor p1 allele, P1-wr, is composed of multiple head-to-tail tandemly arranged copies of the complete gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 59 publications
4
39
0
Order By: Relevance
“…The rate of occurrence of aberrant phenotypes is higher than observed for normally propagated plants and appears to reflect a higher "mutagenic" rate during tissue culture. Detailed characterization of particular somaclonal variants has revealed evidence for novel TE insertions as well as epigenetic changes (Rhee et al 2009(Rhee et al , 2010. It is worth noting that the consistent DNA methylation changes observed in this study and in a prior study in rice (Stroud et al 2013) would predict a tissue culture "syndrome" that would be observed in many of the plants regenerated from culture.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The rate of occurrence of aberrant phenotypes is higher than observed for normally propagated plants and appears to reflect a higher "mutagenic" rate during tissue culture. Detailed characterization of particular somaclonal variants has revealed evidence for novel TE insertions as well as epigenetic changes (Rhee et al 2009(Rhee et al , 2010. It is worth noting that the consistent DNA methylation changes observed in this study and in a prior study in rice (Stroud et al 2013) would predict a tissue culture "syndrome" that would be observed in many of the plants regenerated from culture.…”
Section: Discussionsupporting
confidence: 69%
“…Somaclonal variation has been well characterized in a number of plants species, and generally results in the occurrence of unexpected phenotypes in progeny that arise from tissue culture (Kaeppler and Phillips 1993;Kaeppler et al 2000;Thorpe 2006;Rhee et al 2010;Miguel and Marum 2011;Neelakandan and Wang 2012). The rate of occurrence of aberrant phenotypes is higher than observed for normally propagated plants and appears to reflect a higher "mutagenic" rate during tissue culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue culture-induced epigenetic somaclonal variation of an endogenous gene was demonstrated in maize by identifying novel epialleles of a myb transcription factor, pericarp color 1, which affects the flavonoid biosynthesis pathway in maize seeds (Rhee et al 2010). The progenitor allele, P1-wr, consists of tandem copies of the gene and produces brick-red color in the cob glume.…”
Section: Dna Methylationmentioning
confidence: 99%
“…1. It has been suggested that such epigenetic changes during tissue culture are a major source of somaclonal variation (Kaeppler et al, 2000;Rhee et al, 2010;Miguel & Marum, 2011;Neelakandan & Wang, 2012;Stelpflug et al, 2014;Ong-Abdullah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%